Two cities by water and against water, Santiago (Chile) and Murcia (Spain): heritage from the river as an element of foundation and destruction - Castejón Porcel, Gregorio (Investigaciones Geográficas, 2020)
The cities of Santiago and Murcia, despite the historical differences in their genesis and evolution, have an identity condition that makes them sites whose existence is marked by the same geographical element, the river. As it is exposed in this work, based on a comparative study based on a bibliographic and documentary analysis and field work, in both cases the flows of these streams served to irrigate a cultivation space that guaranteed the development of the cities; and, in addition, in the same way, both cities have survived defending themselves against the flash floods by means of the construction of the similar channeling infrastructures. Consequently, the domestication works for the agricultural and industrial use of the waters as well as the defense works, gave rise to a heritage of enormous value and relevance, whose safeguarding and promotion is shown to require greater consideration, protection and cultural and tourist promotion.